First Language Interference and Form Focused Instruction - Shafaq Fayyaz; Suyansah Swanto; Wardatul Akmam Din (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2017)
This paper addresses EFL/ESL teachers’ beliefs and practices regarding the use of the first language in a language classroom pertaining to the Form-Focused Instruction - a grammar instruction approach. In essence, this study looks into whether the judicious use of L1 in learning the foreign or second language is effective or not. A case study strategy was deemed appropriate for this study to explore and investigate the beliefs and practices of the non-native teachers on the use of L1 in learning English as a foreign language. To this end, six English language teachers were selected from a Chinese secondary school. The data were collected through classroom observations and stimulated recall interview questions. The audio-recorded data were fully transcribed in English, and subjected to a process of interpretative analysis. The findings revealed that teachers used L1 mainly to present the target grammar topics, to explain the grammatical rules and also to encourage students for the explanation of the grammatical rules in there L1. It is therefore imperative to consider the results of this study as it may highlight some notable pedagogical implications regarding the assisted effects of the use of first language on foreign/second language learning.